Nutritional Responses of Citrus Rootstocks to Salinity: Performance of the New Hybrids Forner-Alcaide 5 and Forner-Alcaide 13 - Forner-Giner, María A.; Legaz, Francisco; Primo-Millo, Eduardo; Forner Valero, Juan B. (2017)
This study assesses the nutritional behavior of the new citrus rootstocks Forner-Alcaide no.5 (FA-5) and Forner-Alcaide no. 13 (FA-13) under saline conditions compared to that of their parents, Cleopatra mandarin (CM) and Poncirus trifoliata (PT). Eighteen month-old plants grafted with Valencia orange scions were used in the experiment. The plants were grown in a greenhouse and irrigated over an. eight-week period with nutrient solutions to which, different amounts of sodium chloride (NaCl) had been added, namely 0, 20, 40 and 60 mM. Relative growth and the uptake of major mineral elements [nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), and magnesium (Mg,)] were then determined. It was noted that the reduction in relative growth caused by salt treatment was greater in plants grafted on PT than those on FA-13, FA-5 and CM. increasing the salt level in the growth medium reduced the absorption of the above mineral elements in all scion-rootstock combinations. However; this decrease was generally more marked in plants grafted on PT than in those on CM and FA-5. Plants on FA-13 showed an intermediate behavior Positive correlations were found between growth and mineral element uptake by salt treated plants. Nutrient uptake was also plotted against chloride (Cl) and sodium (Na) concentrations in leaves and roots at increasing salt levels. This showed that N absorption was closely correlated (inversely) with Cl content in leaves, whereas K, Ca and Mg uptakes were correlated (inversely) with Na concentration in roots. This suggests that the accumulation of saline ions impacts growth and nutrient uptake by citrus plants.